Some Problems of Solar Quiescent Prominences in the Light of Ambartsumian's Ideas - Nikoghossian, A.
The report is a brief overview of our results in the theory of spectral line formation in atmospheres with complex fine structure. The research motivation was due to interpretation of the EUV spectrum of solar quiescent prominences observed with the SUMER spectrograph as a part of the SOHO space program. We describe the methods proposed for solving the line-radiation transfer problems in multicom- ponent atmospheres which use Ambartsumian's ideas proposed in the theory of radiation transfer and its applications. It is demonstrated that even the simplest static model radiating medium composed of physically different types of elements shows line profiles differing from those formed in the medium with preliminarily averaged properties. The more realistic and complicated case of a multicomponent atmo- sphere with randomly varying properties is considered with special attention paid to the effect of the velocity field. An important role of the relative mean square deviation of observed line intensities in the diagnostics of physical features of spatial and temporal variations of prominences is shown.
Keywords: Solar System studies